Challenges facing smokers in Saudi Arabia - Salama, Ragaa (International Journal of Health Sciences, 2012)
Tobacco smoking causes nearly one fifth of cancer deaths worldwide. The International Agency for Research on Cancer predicts 10 million tobacco-related deaths annually by 2020, of which nearly three forth will be in developing countries. (1) Although Kingdom of Saudi Arabia has a population of about 20 millions, it is the fourth in the world in terms of tobacco sales. (2, 3) The prevalence of smoking for males ranges between 13 to 38% (average 26.5%), while for females it ranges from 1 to 16% (average 9%). (4) Smoking prevalence among students was estimated to be at 14.5%, among those 32.7% males and 5.9% females. The risk factors predispose for smoking among males were age, father's smoking habits and friends' smoking habits; while among females were sister's smoking habits and friends' smoking habits. (5) Young adult smokers from Saudi Arabian University exhibited lower levels of fractional exhaled nitric oxide compared to nonsmokers. This could be an early indicator of effects of smoking on lungs. (6) Toxic effects of tobacco smoking are widely known but the shocking data about its health injuring effect are frequently ignored and less disseminated. It causes between 80-90% of all lung cancer deaths and increases the risk of other cancers (e.g., bladder, oral cavity and esophagus), cardiovascular disease (e.g., myocardial infarction, stroke), lung diseases (e.g., emphysema, bronchitis), and infectious diseases. In addition, the economic burden caused by tobacco smoking is also eating precious resources of the young government. (7) It is one of the most common forms of nicotine dependence (ND) and, is defined as an addictive disorder by Diagnostic and Statistical Manual of Mental Disorder or International Classification of Diseases. Moreover, ND is one of the most prevalent and, most fatal psychiatric disorders where 30-50% of current smokers will die of tobacco-related disorders. Consequently, smoking is still a leading major public health world concern wide. The World Health Organization recently estimated over 1 billion smokers in the world with tobacco use rapidly rising in the developing countries. (8) The secondhand smoke (SHS) contains at least 250 known toxicants generated by the burning of tobacco. The ozone can react with chemicals in SHS to produce ultrafine particles less than 100 nm in diameter. The American Heart Association determined that SHS is a cause of fatal cardiovascular diseases. The third hand smoke (THS) is generally considered to be residual nicotine and other chemicals left on a variety of indoor surfaces by tobacco smoke. This residue is thought to react with common indoor pollutants to create a toxic mixture. This toxic mixture of THS contains cancer-causing substances and poses a potential health hazard to nonsmokers who are unwillingly exposing to it, especially children. (9) The important fact is that no level of smoking or exposure to SHS is safe, even at the lowest detectable levels of exposure, some changes in gene expression within the cells lining the respiratory airways have been reported. (10)